2020
DOI: 10.1609/aaai.v34i02.5530
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Propagators for String Edit Distance Constraints

Abstract: The computation of string similarity measures has been thoroughly studied in the scientific literature and has applications in a wide variety of different areas. One of the most widely used measures is the so called string edit distance which captures the number of required edit operations to transform a string into another given string. Although polynomial time algorithms are known for calculating the edit distance between two strings, there also exist NP-hard problems from practical applications like schedul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Using state-of-the-art CP solvers, the exact approach could be successfully used to find optimal solutions for 7 of the smaller-sized benchmark instances of the PSSP. The CP approach was later improved in Winter et al (2020) with the introduction of a string edit distance global constraint, which could be used to efficiently model parts of the objective function of the PSSP leading to much faster optimality proofs for the smaller instances. However, experiments further showed that the exact approach is not able to produce solutions for instances 11-24, and therefore, the simulated annealing-based approach currently represents the state-of-the-art solution method for larger instances.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Using state-of-the-art CP solvers, the exact approach could be successfully used to find optimal solutions for 7 of the smaller-sized benchmark instances of the PSSP. The CP approach was later improved in Winter et al (2020) with the introduction of a string edit distance global constraint, which could be used to efficiently model parts of the objective function of the PSSP leading to much faster optimality proofs for the smaller instances. However, experiments further showed that the exact approach is not able to produce solutions for instances 11-24, and therefore, the simulated annealing-based approach currently represents the state-of-the-art solution method for larger instances.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Note that instances 1-12 are considered to be small instances, as the round capacity as well as the number of colors, carrier types, and demands are much smaller than for instances 13-24. Many of these small instances could be previously solved to optimality using exact methods in Winter and Musliu (2021); Winter et al (2020). Instances 13-24 on the other hand represent real-life scheduling scenarios from a large-scale industrial paint shop; therefore, they all use the same round capacity, colors, and carrier types.…”
Section: Experimental Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…[83] • What are the next propagation steps? [65,208] • Which choices should I relax in order to recover consistency? [7,82] • Which choices should I relax in order to render such a value available for such a variable?…”
Section: Constraint Programming (Cp)mentioning
confidence: 99%
“…Similar ideas using a lazy clause generation solver for explaining propagation via constraints from which nogoods can be computed can be applied to string edit distance constraints, e.g. in [208] Winter et al use explanations that consist of literals which logically entail the truth of a Boolean variable that encodes propagation of some variable's value.…”
Section: Emphasis Original]mentioning
confidence: 99%